IDENTIFYING FACTORS THAT AFFECT EMPLOYEE PERFORMANCE - Eric Hermawan; Emaya Kurniawati; Ansari; Rosalina Anindia Sari Kartika; Amin Budiastuti (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to determine the influence of the work environment, work motivation and work discipline on employee performance at PT JNE Branch in Depok City. The research method used in this study uses a quantitative method. The population of employees working at PT JNE Branch in Depok City is 44 people. Determination of the number of samples using the Slovin census so that a sample of 44 people was obtained. The research instrument used a questionnaire and interview list. The results of the quantitative study were analyzed using Eviews 11. The results of the study obtained partially that the work environment, work motivation and work discipline have a positive and significant effect on employee performance at PT JNE Branch in Depok City, while simultaneously that the work environment, work motivation and work discipline have a positive and significant effect on employee performance at PT JNE Branch in Depok City